A4.12 Endothelin-1 Promotes the Endothelial-to-Mesenchymal Transition in Cultures of Human Endothelial Cells. (25th February 2013) - Soldano, S; Brizzolara, R; Sulli, A; Cimmino, MA; Seriolo, B; Montagna, P; Cutolo, M
Abstract : Background and Objectives: Endothelial/microvascular injury and myofibroblast activation are crucial events that seem to contribute to the development of fibrosis in connective tissue diseases such as systemic sclerosis (SSc) [1]. Endothelin-1 (ET-1) contributes to the fibrotic process by inducing myofibroblast activation and increased extracellular matrix (ECM) synthesis [2]. Recently, it has been shown that myofibroblast activation from altered microvasculature may arise from the transition of endothelial-to-mesenchymal cell process (EndoMT), thus expressing α-smooth muscle actin (α-SMA), vimentin and fibrillar collagens [3]. The study investigated the possible involvement of ET-1 in the EndoMT in cultures of human endothelial cells. Material and Methods: Human dermal microvascular endothelial cells (HMVEC, Lonza Clonetic, Switzerland) and human umbilical vein endothelial cells (HUVEC, Lonza), were treated with or without ET-1 (100 nM, Enzo Life Science, UK) for 3 and 6 days. The expression of α-SMA, a marker of myofibroblast phenotype, and platelet endothelial cell adhesion molecule (PECAM-1 or CD31), a marker of endothelial phenotype, were evaluated by immunofluorescence (IF) and western blot analysis (WB) using primary antibodies to human α-SMA (dilution 1:50 for IF and 1:100 for WB, Dako Cytomation, Denmark) and to human CD31 (dilution 1:200 for IF and 1:1000 for WB, CellSignalling Technology, Denver, USA), in accordance with recent evidences [4, 5]. Data were obtained from four different experiments. Results: After 6 days of treatment ET-1 induced the expression of α-SMA in cultures of HUVEC, which maintained their ability to express CD31. Interestingly, ET-1 induced the α-SMA expression also in cultures of HMVEC after 6 days of treatment, without modulating the expression of CD31 when compared to untreated cells and confirming the data obtained in HUVEC cultures. The results were obtained by IF and confirmed by WB. Conclusions: These preliminary results show that ET-1 seems to induce the α-SMA expression in human endothelial cells thus supporting a possible direct involvement in promoting the EndoMT [2, 4–6]. The implications in the fibrotic process that characterise SSc are under evaluation [7]. References: Wynn TA. J Pathol 2008; 214:199–210. Batthacharyya S. et al, Nat Rev Rheumatol 2012; 8:42–54. Piera-Velazquez S. et al, Am J Pathol 2011; 179:1074–80 Widyantoro B. et al, Circulation 2010; 8:2407–18. Kitao A. et al, Am J Phatol 2009; 175:616–26. Abraham D. et al, Arthrit Res Ther 2007; 9:doi.10.1186/ar2186. Soldano S. et al, A&R 2012; 64 (Supplement):S640